BASIC RESEARCH PRINCIPLES OF EFFICIENCY OF AIRCRAFT LAND EQUIPMENT MAINTENANCE SYSTEMS - Лінник, О.; Кравченко, Е. (Science-based technologies, 2012)
Modern methods of efficiency definition of aviation land engineering maintenance systems are examined and the approach to working oui of methodology of programs shaping of aviation land engineering technical maintenance taking into account features of problems which face to aviation transport system is justified: security of the set level of safety and a regularity of flights.